Penggunaan Ragam Bahasa Gaul pada Kolom Komentar Tiktok @Fadiljaidi - Badrotun Nikmah (ESTETIK : Jurnal Bahasa Indonesia, 2022)
Slang in 2021 is often used by the public, especially teenagers, this can happen due to the increasingly widespread use of social media. One of them is the Tik Tok application, during the pandemic this application was very popular with all Indonesian people. This study aims to: 1) Describe the forms of slang in @fadiljaidi's TikTok comment column 2) Describe the meaning of slang in @fadiljaidi's TikTok comment column. The data used is slang written in the comments column. Data Collection Techniques using the listen and note technique method, the author carefully reads the comments on the @fadiljaidi account and then records slang words as research data. The data analysis technique used an agih method, by explaining the language with the language itself. The results of this study are to classify slang into 3 forms: 1). Combining words: Nobar, Salfok, Gaptek, Mabar. 2) Reversing words with words: Ucul, Kane, Kuy, Ngab. 3) Phrases: Ngadi-ngadi, Ngakak banget, Bengek, Gemoy, Gumush, Receh, Wadoeh, Mengcape